Identifikasi dan Analisis Filogenetik Ikan Ekonomis Penting Oreochromis sp. dengan Pendekatan DNA Barcoding - Reny Sianturi; Muhammad Dailami; Dandi Saleky (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Species identification is one of the most basic and important factors in fisheries management. Oreochromis sp., such as tilapia (Oreochromis mosambicus) and tilapia (Oreochromis niloticus) are introduced species of fish originating from outside Merauke which are now the dominant fish and are commonly found in inland waters of Merauke. The purpose of this study was to identify the economically important fish species Oreochromis sp. which landed at Merauke Traditional Market with DNA Barcoding approach. DNA amplification with the COI gene resulted in a DNA sequence length of 655 bp with the identification result being Tilapia (Oreochromis niloticus). Based on the phylogenetic tree data and genetic distance, the DNA sequences of the samples formed the same clade as the Oreochromis niloticus sequences from GeneBank with 0% genetic distance and it was estimated that these species came from the same parents. Identification with DNA Barcoding makes it easy to identify species quickly and accurately.